PENINGKATAN KUALITAS KESEHATAN MASYARAKAT MELALUI METODE GARDENING THERAPY UNTUK MENURUNKAN GLUKOSA DARAH PADA PENYANDANG DM DI DESA BINONG - Elysabeth Sinulingga; Fiolenty B. Marulianna Sitorus; Marisa Manik; Juwita Fransiska Br Surbakti; Heman Pailak (Asosiasi Sinergi Pengabdi dan Pemberdaya Indonesia (ASPPI), 2025)
The Community Service Activity (PKM) in Binong Village addresses the high prevalence of Type II Diabetes Mellitus (DM) and the limited knowledge of non-pharmacological therapies among patients. This initiative focuses on improving patient health through gardening therapy, which also serves as a practical, low-cost solution to reduce the economic burden of medication. The primary objective of this PKM is to enhance participants' understanding of DM management and increase their physical activity. The program was implemented in two stages. The first stage involved an educational session evaluated with pre- and post-quizzes. The results showed a significant improvement in knowledge, with the average score rising from 53.29 to 66.33 among 40 participants, a gain of 13.04 points. The second stage featured a competition where participants grew herbal plants like bay leaves, basil, and red betel leaves. The judging panel assessed the plants at the participants' homes in the third month. The overall outcomes demonstrate that the activity was effective in boosting participants' knowledge of gardening therapy and encouraged them to use their homegrown herbal plants to help manage their daily blood sugar levels.